Comparison of Lewis Acidity between Al-MCM-41 Pure Chemicals and Al-MCM-41 Synthesized from Bentonite - Tewfik Ali-Dahmane; Lamia Brahmi; Rachida Hamacha; Salih Hacini; Abdelkader Bengueddach (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
This study focused on the Lewis acidity of Al-MCM-41 prepared from bentonite (Al-MCM-bentonite) as silica and aluminum source simultaneously. This acidity was compared with Al-MCM-41 synthesized from pure chemicals reagents (Al-MCM-standard). Structural analysis showed that the substitution of the silicon atom by the aluminum atom decreases the structural order of Al-MCM-standard, whereas Al-MCM-bentonite has a better structural organization. The Lewis acidity of the Al-MCM-bentonite was evaluated in allylation reaction of benzaldehyde with allyltrimethylsilane and pyridine adsorption experiments. The results showed that the difference in acidity between Al-MCM-standard and Al-MCM-bentonite is due to the amount of aluminum incorporated into the framework of our mesoporous materials. According to the EDX analysis, the incorporation of aluminum in Al-MCM-standard (Si/Al = 13.47) is more important than in Al-MCM-bentonite (Si/Al = 43.64). This explains the low acidity of Al-MCM-bentonite, and the moderate yields in the allylation reactions of benzaldehyde with allyltrimethylsilane.